The Technology of Utilizing Microorganism in Feed to Improve Ruminant Productivity in Indonesia: A Review - Wina, Elizabeth (Indonesian Animal Sciences Society, 2005)
Several different technologies are required to inaintain feed availability, to improve feed quality and to optimize rumen function so that the animal production in Indonesia can be increased. The technology by utilizing microorganism in food has been known for a long time. Utilization of microorganism could be in the forms of probiotic (bacteria, fungi, yeast or their mixtures), fermentation products or extracted products of fermentation process (enzymes). This paper describes several research results that have been published locally in recent years about the utilization of microorganism or its products in ruminant feed. Several pure microorganisms or mixtures of microorganisms have been available commercially and some of them are also produced and developed by the Indonesian Research Institute for Animal Production. They have been applied for rice straw fermentation, for improving the quality of agricultural by products such as palm oil by products or for improving the rumen function. Biological treatment using microorganism has a good prospect in the future, however, it should be supported by more specific and deeper research about the characteristics of the microorganisms. A standard and feed safety regulation on the use of single or mixture of microorganism is required to be established. Keywords: Microorganism, probiotic, silage, fennentation, ruminant